Agricultural pests' recognition using deep learning and ChatGPT - Aung, Su Myat (Nanyang Technological University, 2024)
The issue of global food security has become a pressing concern, with the growing population and the increase in demand for food. However, agricultural crop losses due to pest infestation pose a significant challenge to the sustainability of food security. To address this challenge, the adoption of smart agriculture practices stands as the optimal strategy for farmers. By leveraging on the artificial intelligence techniques alongside modern information and communication technology, farmers can effectively combat pest infestations and mitigate crop losses. Furthermore, the emergence of generative AI, exemplified by ChatGPT, represents a rapid advancement in technology. These systems have the capability to offer natural language explanations and tailored suggestions for users.